Pelatihan Proses Cutting dan Drilling Bagi Mahasiswa di Growth Centre LLDIKTI Wilayah - I - Siregar, Amru; Darianto, Darianto; Apriliya, Indah; Mahyunis, Mahyunis (CV. IRA PUBLISHING, 2023)
Cutting and drilling training is a program designed to provide the necessary knowledge and skills for students to cut and form holes in materials. During the training, participants will learn the basic principles and effective cutting techniques using various cutting tools such as hand saws, hacksaw machines, and grinding machines. Participants will also be taught about the proper use of drilling machines and techniques. The trainee will gain an in-depth understanding of selecting suitable cutting tools, machine settings, appropriate cutting speeds and safe handling during the cutting and drilling process. Participants will also be trained in measuring and evaluating the quality of cutting and drilling results. After completing the training, participants are expected to have practical skills in operating cutting machines and drilling machines. Participants can perform cutting and drilling with precision, efficiency and good quality. Participants will also increase their understanding of solving problems related to cutting and drilling. Thus, cutting and drilling training will significantly benefit participants in improving skills, work efficiency, and safety in material cutting and drilling operations.